2011
DOI: 10.1007/s13197-011-0506-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of zero-trans non-interesterified and interesterified shortenings in cookie production

Abstract: The effects of zero-trans chemically interesterified (in-es) and non-interesterified (non-in-es) cottonseed (CO), hazelnut (HO) and olive oil (OO) and their blends (25, 50 and 75%) with palm oil (PO) were studied in the production of cookies. All the experimental shortenings had zero-trans fatty acids (TFA) while the shortening contained 14.20% TFA. Incorporation of CO in PO considerably increased the linoleic acid content whereas the raising of HO and OO ratio in the blend increased the oleic acid content. Ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…It contained saturated fatty acid (SFA) (40.8-42.3%), monounsaturated fatty acid (MUFA) (52.9-55.0%) and polyunsaturated fatty acid (PUFA) (2.5-3.4%). On the other hand, the palm oil contained SFA (50.5%) and monounsaturated fatty acids (49.5%) (Dinc et al 2011). Thus, the fatty acid composition of simarouba oil somewhat resembles with palm oil.…”
Section: Resultsmentioning
confidence: 93%
“…It contained saturated fatty acid (SFA) (40.8-42.3%), monounsaturated fatty acid (MUFA) (52.9-55.0%) and polyunsaturated fatty acid (PUFA) (2.5-3.4%). On the other hand, the palm oil contained SFA (50.5%) and monounsaturated fatty acids (49.5%) (Dinc et al 2011). Thus, the fatty acid composition of simarouba oil somewhat resembles with palm oil.…”
Section: Resultsmentioning
confidence: 93%
“…Hence this method could assist in eliminating the posthardening phenomena, which was very notorious in PS-based fats [10]. Blends of PS with other oils (rice bran oil, canola oil, sesame oil, and soybean oil) and fats provided good plasticity and consistency [10,12,14]. Results herein demonstrated that the combination by direct blending of PS with HOSO could provide an array of new fat products with the desired consistency.…”
Section: Consistencymentioning
confidence: 82%
“…These processes are aimed to impart the desired functionality without generating TFA [10][11][12]. Direct blending has several advantages compared to either CI or EI [13,14], the most relevant being that no chemical processes are involved, and is consistent with the consumer trend toward consumption of natural products [13].…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…International and national policies on trans fatty acids (TFAs): As a result of growing interest in nutritional health, different governmental and nongovernmental organizations have based their recommendations upon addressing noncommunicable diseases (NCDs) including obesity as causes of nearly one million deaths annually in the Middle East and North Africa (15,16). In recent years, different approaches such as education, food labeling and enacting legislations have been pursued in this regard to minimize TFAs intake worldwide (17).…”
mentioning
confidence: 99%